Oral Rehabilitation of a Patient with Congenital Erythropoietic Porphyria: A Rare Case Report - Alan, Raif; Kilinc, Fahriye; Dursun, Recep; Çelebi, Hakkı (UI Scholars Hub, 2020)
Congenital erythropoietic porphyria (CEP) is an extremely rare disorder involved in chronic porphyrias. One of the recommended evaluations to determine disease severity and needs of a person with CEP is dental assessment. Objective: To present a case of CEP and its oral rehabilitation. Case Report: A 32-year-old female patient was admitted to the clinic with hyperkeratinization, skin fragility, fissures, and wounds in her perioral region and hands. Intraoral gingival bleeding, mucogingival stress, and missing teeth were recorded. After medical consultation, phase I and II periodontal therapies were performed. The patient expressed satisfaction of the results of the procedures in terms of the parameters evaluated. The rare occurrence of the disease may delay the diagnosis. An unmet need still exists for multidisciplinary orientation of patients with CEP. Conclusion: Dentists should have and follow guidelines for treating patients with CEP.